(-9y+5)-8(-y-2)y=3

Simple and best practice solution for (-9y+5)-8(-y-2)y=3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (-9y+5)-8(-y-2)y=3 equation:


Simplifying
(-9y + 5) + -8(-1y + -2) * y = 3

Reorder the terms:
(5 + -9y) + -8(-1y + -2) * y = 3

Remove parenthesis around (5 + -9y)
5 + -9y + -8(-1y + -2) * y = 3

Reorder the terms:
5 + -9y + -8(-2 + -1y) * y = 3

Reorder the terms for easier multiplication:
5 + -9y + -8y(-2 + -1y) = 3
5 + -9y + (-2 * -8y + -1y * -8y) = 3
5 + -9y + (16y + 8y2) = 3

Combine like terms: -9y + 16y = 7y
5 + 7y + 8y2 = 3

Solving
5 + 7y + 8y2 = 3

Solving for variable 'y'.

Reorder the terms:
5 + -3 + 7y + 8y2 = 3 + -3

Combine like terms: 5 + -3 = 2
2 + 7y + 8y2 = 3 + -3

Combine like terms: 3 + -3 = 0
2 + 7y + 8y2 = 0

Begin completing the square.  Divide all terms by
8 the coefficient of the squared term: 

Divide each side by '8'.
0.25 + 0.875y + y2 = 0

Move the constant term to the right:

Add '-0.25' to each side of the equation.
0.25 + 0.875y + -0.25 + y2 = 0 + -0.25

Reorder the terms:
0.25 + -0.25 + 0.875y + y2 = 0 + -0.25

Combine like terms: 0.25 + -0.25 = 0.00
0.00 + 0.875y + y2 = 0 + -0.25
0.875y + y2 = 0 + -0.25

Combine like terms: 0 + -0.25 = -0.25
0.875y + y2 = -0.25

The y term is 0.875y.  Take half its coefficient (0.4375).
Square it (0.19140625) and add it to both sides.

Add '0.19140625' to each side of the equation.
0.875y + 0.19140625 + y2 = -0.25 + 0.19140625

Reorder the terms:
0.19140625 + 0.875y + y2 = -0.25 + 0.19140625

Combine like terms: -0.25 + 0.19140625 = -0.05859375
0.19140625 + 0.875y + y2 = -0.05859375

Factor a perfect square on the left side:
(y + 0.4375)(y + 0.4375) = -0.05859375

Can't calculate square root of the right side.

The solution to this equation could not be determined.

See similar equations:

| y=13x^2-7x+5 | | 32-6x+7x=-5+28 | | 5/8(x-1/2)=5/12 | | u^2+8u-65=0 | | 10m-3-2-10m+5= | | 200-1.5=180-0.5 | | HJ=x+60 | | -2[x+3]=-22 | | -18(y+3)+6(4y-3)=5(y-4)+13 | | cos(3x-2)=-0.777 | | 16m-64=0 | | 5x-4(3x+7)=161 | | 5x-7y+2y-9x-5y= | | 4y+7=z | | Y=ln(20) | | 5/1/4 | | 5y=15+3y+3 | | 5(-3y-1)-(6-5y)y=-6 | | 2v=11 | | 3x+12=4x-2x+1 | | [X-4]/2=9 | | x^4+31x^2=180 | | 2/1/10x=5/3/10 | | 1.8855=0.8193x-0.7785 | | 9u+12u=51 | | 4x(x-5)=16 | | x^2=f(x) | | X^4-21x+80=0 | | 2.6x-2.08=9.3-x | | 4x-7=-2x-8 | | y^4-y^2-1=0 | | (x-3).2=12-4x |

Equations solver categories